Effect of structural heterogeneity water-coal fuel conditions and characteristics of ignition; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 82 : Thermophysical Basis of Energy Technologies - Syrodoy S. V. Semen Vladimirovich (2015, 2015)
Title screen